Highly conductive and long-term stable films from liquid-phase exfoliated platinum diselenide - Lee, Kangho; Szydłowska, Beata Maria; Hartwig, Oliver; Synnatschke, Kevin; Tywoniuk, Bartlomiej; Hartman, Tomáš; Tomašević-Ilić, Tijana; Gabbett, Cian P.; Coleman, Jonathan N.; Sofer, Zdeněk; Spasenović, Marko; Backes, Claudia; et al. (Journal of materials chemistry. C, Materials for optical and electronic devices, 2023)
Liquid-phase exfoliation (LPE) has been introduced as a versatile and scalable production method for two-dimensional (2D) materials. This method yields dispersions that allow for the fabrication of printable and flexible electronic devices. However, the fabrication of uniform and homogeneous films from LPE dispersions with a performance similar to that of bottom-up grown materials remains a challenge, as the film quality strongly influences the optical and electrical performance of devices. Furthermore, long-term stability remains a major challenge for all 2D material based applications. In this study, we report on highly conductive tiled network films made of platinum diselenide (PtSe2) flakes derived using a scalable LPE method. We characterized the homogeneous films in terms of morphology and electrical behavior. As an example of applicability, we produce a chemiresistive sensor structure with the PtSe2 films and show significant resistance changes upon periodic ammonia gas exposures, revealing a sub-0.1 part per million (ppm) detection limit (DL). More remarkably the devices are fully functional after 15 months, underlining the high stability of PtSe2 based devices.
Gesehen am 31.01.2023